2016
DOI: 10.1097/md.0000000000002314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Educational Level, Stage, and Histological Type on Survival of Oral Cancer in a Brazilian Population

Abstract: The mortality rate associated with oral cancer is estimated at approximately 12,300 deaths per year, and the survival rate is only 40% to 50% for diagnosed patients and is closely related to the duration of time between disease perception and its diagnosis and treatment. Socioeconomic risk factors are determinants of the incidence and mortality related to oral cancer. We conducted a retrospective, cross-sectional study of 573 records of patients with oral cancer at Haroldo Juaçaba Hospital – Cancer Institute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
27

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 29 publications
6
46
1
27
Order By: Relevance
“…It was also observed, similar to the present study, that patients with low education and high immunoexpression for TNF-α showed a worse survival rate, in addition to greater staging and use of surgery associated with radiotherapy and chemotherapy as a treatment of choice (Krishnan et al, 2014). In previous studies, patients with stage III and IV tumours expressed more TNF-α; in the researchers' country, patients with advanced disease stage are patients with a low level of education (Ferreira et al, 2012;Dantas et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was also observed, similar to the present study, that patients with low education and high immunoexpression for TNF-α showed a worse survival rate, in addition to greater staging and use of surgery associated with radiotherapy and chemotherapy as a treatment of choice (Krishnan et al, 2014). In previous studies, patients with stage III and IV tumours expressed more TNF-α; in the researchers' country, patients with advanced disease stage are patients with a low level of education (Ferreira et al, 2012;Dantas et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…This tumour growth results in a greater tumour staging that is linked to worse prognosis and higher mortality (Iamaroon et al, 2004). A previous study conducted by this group of researchers (Dantas et al, 2016) also observed that schooling directly influences patient survival. Oral cancer is related to low education, which may be partly due to poor access to disease information in general, including the diagnosis and treatment of oral cancer (Atununes et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Although smoking generates a risk factor for oral SCC that is purely biological, it is known that the risk of developing oral cancer is increased in individuals with low education levels, low occupational classes and low incomes (Conway et al, 2008). Oral SCC is a type of cancer that has a relationship with social status, showing a worse prognosis in patients with lower socioeconomic status (Dantas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Survival was calculated as the time from the treatment start date (day, month and year) to the date of death (day, month and year) in number of weeks for statistical analysis (Dantas et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A sobrevida foi obtida por meio da diferença entre a data do início do tratamento (dia, mês e ano) e a data do óbito (dia, mês e ano) utilizando para fins de análise estatística a quantidade de semanas entre essas datas 9 .…”
Section: Métodounclassified